A World Constitution in the key of human rights from the periphery of the world - Tobar Rodríguez, Javier Antonio; Rodríguez Arias, Manuel Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of this article was to reflect on the current situation of constitutionalism in relation to the pandemic from the periphery, that is, Central America and especially El Salvador in relation to the outside of the world. We use the direct observation of reality, especially of the events that occurred recently and priorto the occurrence of the pandemic and coexisting with it, detecting ideas in common with which we intend to maintain that the future of the human race should be reflected upon and that the instrument optimal legalcohesion is a global constitution that contains minimums as an instrument of uniform law. At this point of no return in the history of humanity, we grant ourselves license to think freely and go beyond the limits of the political impossibility required to make constitutional changes, which involves blurring borders, to recognize minimum rights of humanity. The result of this mission cannot be more than to recognize universal minimum rights, mainly of the most vulnerable populations on the planet. Putting the results into practice implies using a high dose of imagination, leaving behind preconceived ideas and broadening the horizon of the proposal, which is necessary as soon as the rights of humanity are made concrete.